Data analysis of CSI 800 industry index by using factor analysis model. (9th August 2019) - Xu, Chunfen
This paper studies the linkages among the industries based on CSI 800 industry index, which provides mass complicated data for industry research. Factor analysis, a useful data analysis tool, allows researchers to investigate concepts that are not easily measured directly by collapsing a large number of variables into a few interpretable underlying factors. Firstly, data of ten industries in the period from September 2009 to March 2017 is collected from CSI 800 Index and correlational analyses are conducted. Secondly, this paper establishes an appropriate evaluation system, and then uses factor analysis to do dimension reduction. Finally, some characteristics and trends in various industries are obtained.